STUDI KOMPARATIF PENGUJIAN MANUAL DAN PENGUJIAN OTOMATIS DENGAN CYPRESS PADA WEBSITE - Kamisr, Rahayu Amaliyah (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This study aims to compare the effectiveness of manual testing and automated testing using Cypress on the Mangkasir website, a web-based point of sales (POS) system. The research method used is a comparative study with a quantitative approach, involving direct testing of key features such as login, product management, transactions, and store management. Data were collected based on execution time and test case results for both methods. The testing results indicate that automated testing provides faster execution, higher consistency, and greater script reusability compared to manual testing, which is generally slower and prone to human error. Although several features could not be tested comprehensively due to technical limitations, the findings recommend the adoption of automated testing as a more efficient solution for software testing, especially in repetitive testing scenarios.